PENGARUH OPINI AUDITOR DAN RASIO FUNDAMENTAL TERHADAP HARGA SAHAM PERUSAHAAN DI BURSA EFEK INDONESIA: Bahasa Indonesia - RAHMADI, FUJI SRI; Efriyenti, Dian Efriyenti (SCIENTIA JOURNAL, 2021)
Stock price growth on the LQ 45 index also shows that the stock price for 5 years has grown by -24% while the auditor's opinion is reasonable, ROA, CR and DER fluctuate which tends to decrease. This study aims to determine the effect of auditor's opinion, ROA CR and DER on company stock prices on the LQ 45 index. The data used are secondary data in the form of annual financial statements published in the 2015-2019 period of 27 companies. testing in the form of classical assumptions, multiple linear regression and hypothesis testing using SPSS. 22. The results of the study partially show Auditor Opinion has a significant positive effect on Stock Prices, ROA (Return On Assets) has a significant effect on Stock Prices, DER (Debt Equity Ratio) has a negative but not significant effect on Stock Prices, CR (Current Ratio) has a negative effect but not significant to the Share Price. Simultaneously Auditor Opinion, ROA, DER and CR have a significant effect on stock prices. Keywords: Current Ratio;Debt Equity;Return On Asset;Price; Opinion